2020
DOI: 10.3390/polym12081853
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Degradation of Electrospun Poly(Lactic-Co-Glycolic Acid) (PLGA) for Oral Mucosa Regeneration

Abstract: Poly(lactic-co-glycolic acid) (PLGA) has been used in the field of tissue engineering as a scaffold due to its good biocompatibility, biodegradability and mechanical strength. With the aim to explore the degradability of PLGA electrospun nonwoven structures for oral mucosa tissue engineering applications, non-irradiated and gamma irradiated nonwovens were immersed in three different solutions, in which simulated body fluid (SBF) and artificial saliva are important for future oral mucosa tissue engineering. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…Inactive apoptosis of cancer cells results in low mortality of malignant cells [ 30 ]. Many previous studies [ 31 34 ] have shown that PTX can induce apoptosis of cancer cells to a certain extent. Yuan et al [ 35 ] also reported that the PTX delivery system based on PLGA-Tween 80 copolymer can significantly induce apoptosis of A549 cells and thus play a therapeutic role in vitro, which is similar to our research results.…”
Section: Resultsmentioning
confidence: 99%
“…Inactive apoptosis of cancer cells results in low mortality of malignant cells [ 30 ]. Many previous studies [ 31 34 ] have shown that PTX can induce apoptosis of cancer cells to a certain extent. Yuan et al [ 35 ] also reported that the PTX delivery system based on PLGA-Tween 80 copolymer can significantly induce apoptosis of A549 cells and thus play a therapeutic role in vitro, which is similar to our research results.…”
Section: Resultsmentioning
confidence: 99%
“…With an increasing testing time, a diminish in the intensity of carbonyl originating from copolymer’s ester bonds (~1750 cm −1 ) was observed, accompanied by the appearance of a new peak at ~1710 cm −1 . This lower wavenumber band was particularly associated with vibrations of hydrogen-bounded carbonyl from carboxylic acids, such as LA and GA resulted from SBF-mediated hydrolysis of PLGA [ 72 , 73 ]. At the same time, more pronounced maxima and spectral widening occurred in the 3000–2850 cm −1 region, as a result of overlapped –CH and O–H vibrations, also originating from carboxylic acids.…”
Section: Resultsmentioning
confidence: 99%
“…In one study, porcine smooth muscle cells grew on PLGA nanofibers for 30 days after which growth slowed [51]. PLGA nanofibers have been shown to shrink in fluids including Dulbecco's Modified Eagle Medium (DMEM), simulated body fluid (SFB), and saliva [52]. This is due to fluid-induced relaxation of the polymer chain and can increase hydrolytic and enzymatic degradation.…”
Section: Poly(lactic-co-glycolic) Acid-poly(lactic-co-glycolicmentioning
confidence: 99%
“…Any implantable medical device also has to undergo sterilization, which has also been shown to speed the degradation of PLGA. Chor et al [52] found that gamma irradiated electrospun PLGA scaffolds had low polymer molecular weight and enhanced hydrolytic degradation in SBF and saliva compared to nonirradiated scaffolds. Since PLGA undergoes bulk erosion, the mechanical properties of PLGA decrease as it degrades and may pose a problem for the long-term patency of a PLGA TEVG, especially, if it degrades before substantial remodeling and integration can occur.…”
Section: Poly(lactic-co-glycolic) Acid-poly(lactic-co-glycolicmentioning
confidence: 99%